Assessment of Mastic tree (Pistacia lentiscus L.) plantations in Çeşme-İzmir, Turkey (Theoretical and Applied Forestry, 2023)
Today, non-wood forest products obtained from forests have a very important role for humans. Mastic tree is an important non-wood forest product plant. In this study, the growth and development of three mastic tree plantation areas established in 2016 in Çeşme-İzmir were evaluated. The mean height, diameter, crown diameter and last year shoot length of mastic tree seedlings were found to be 121,91 cm, 6,37 cm, 176,59 cm and 3,63 cm, respectively. Plantation areas showed statistically significant differences in terms of all explored characteristics. Positive associations of crown diameter with height and diameter were found in all studied plantation areas. This study revealed that the growth and development status of the mastic tree seedlings in the evaluated plantation areas in Çeşme-İzmir are good. However, it should not be overlooked that identifying the growth and development status of mastic tree in the longer term will produce more beneficial results for practitioners.
Keywords: Plantation; Çeşme; Non-wood forest product; Pistacia lentiscus